Effect of environment × cultivar interaction on protein and mineral contents of alfalfa (Medicago sativa L.) in Central Anatolia, Turkey - Özköse, Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2018)
Nutritive value and persistence of different alfalfa cultivars, but very little information is available in the literature on mineral concentrations, especially on microelements. This study was carried out to determine crude protein and mineral contents in alfalfa cultivars from two different locations, Ankara and Konya provinces, in Central Anatolia during 2005 and 2007. The experiment was conducted using a randomized complete block design with three replications. Significant differences in many investigated traits were found between cultivars, years, locations and location x year, location x cultivar, year x cultivar, and location x year x cultivar interactions. A crude protein ratio and micro and macro element contents (K, P, Mg, Ca, Mn, Fe, Zn, B, Mo, Cu, Cr, Se and Al) were analyzed in alfalfa on a dry weight basis. The results showed that the protein content ranged 17.23 to 20.71%. The macro element contents ranged 2.06 to 3.95 g kg–1 for K, 13.65 to 23.25 g kg–1 for P, 1.31 to 2.53 g kg–1 for Mg, 6.71 to 22.81 g kg–1 for Ca, and 44.3 to 92.7 mg kg–1 for Fe, whereas the microelement contents ranged 15.4 to 54.3 mg kg–1 for Mn, 24.6 to 121.9 mg kg–1 for Zn, 46.4 to 85.4 mg kg–1 for B, 0.50 to 6.13 mg kg–1 for Mo, 3.13 to 4.17 mg kg–1 for Cu, 0.93 to 2.40 mg kg–1 for Cr, 0.77 to 1.03 mg kg–1 for Se and 31.2 to 57.8 mg kg–1 for Al. Significant differences at the p<0.01 or p<0.05 level in many investigated traits were found between cultivars, years, locations and location × year, location × cultivar, year × cultivar, and location × year × cultivar interactions. In conclusion, due to the fact that the location × year × cultivar interaction was found statistically significant, we suggest that appropriate cultivars are selected for each region.